Analog Resources and Digital Limitations: Navigating Old Norse Academia as an Early-Career Scholar - Perabo, Lyonel (Septentrio Conference Series, 2021)
See RECORDING. Following the completion of a bachelor in History, started in France but completed in Tromsø as an exchange student, I started to develop an interest for Scandinavian History and culture, which translated in me moving to Iceland to enroll in the Old Norse Religion MA program at the university of Iceland in 2013. After graduation, three years later, I began the life of an unaffiliated early-career scholar eager to make use of my newly-acquired knowledge. Since then, I have met with a number of obstacles related to access to scientific publications and source material, as well as discovered and developed ways around such problems. Working largely outside the framework of a higher-education establishment, my academic experience has so far been characterized by the mixing of traditional research methods and resources with more informal approaches. Finding primary sources, always a capital task for researchers of older History, is the perfect example of how contemporary Old Norse scholars combine long-established resources such as scholarly editions and manuscript transcription with less well-established web-based material such as amateur translations and commentaries. Online support and networking groups, largely operating via social media pages also do play an important role in facilitating collaboration between scholars, wanna-be scholars, and other enthusiasts, as well as making less-accessible resources more widely-distributed. One such example of collaborative internet-based academic project is the current Old Norse translation network I have been a part of since last year. Gathering individuals currently or formerly employed in academia, as well as enthusiastic amateurs and prospective academics, it makes for a relevant case study. This can be used to demonstrate how contemporary Old Norse scholars must operate in a hybrid field where the ever-growing amount of online resources must nevertheless be critically balanced with traditional published sources in order to conduct research.